The 2007 Dutch Reformed Church Synod Resolution: Impact on gay ministers - Loggerenberg, Marietjie van (HTS teologiese studies, 2015)
At the 2007 General Synod of the Dutch Reformed Church (DRC), a compromise resolution was accepted regarding homosexual members. The resolution, inter alia, requires of gay ministers to remain celibate as a prerequisite to be legitimated. This research is a qualitative inquiry to evaluate the impact this resolution has on the lives of gay ministers and gay candidate ministers. Apart from doing a literature study Narrative and Post-foundational perspectives were obtained by interviewing six gay ministers and/or candidate ministers as co-researchers, and also by engaging in dialogue with interdisciplinary experts from Sociology, Psychology and Law. From the stories told by the gay ministers and/or gay candidate ministers, certain themes emerged, revealing the immense impact caused by the resolution.